Synthesis of Co,Ce Oxide Nanoparticles Using an Aerosol Method and Their Deposition on Different Structured Substrates for Catalytic Removal of Diesel Particulate Matter - Godoy, Maria Laura (2023)
The synthesis of Co and Ce oxide nanoparticles using precipitation of precursor salt solutions in the form of microdroplets generated with a nebulizer proved to be an efficient, fast and inexpensive method. Different morphologies of single oxides particles were obtained. Ceria nanoparticles were almost cube-shaped of 8 nm average size, forming 1.3–1.5 μm aggregates, whereas cobalt oxide appeared as rounded-edged particles of 37 nm average size, mainly forming nanorods 50–500 nm. Co3O4 and CeO2 nanoparticles were used to generate structured catalysts from both metallic (stainless steel wire mesh monoliths) and ceramic (cordierite honeycombs) substrates. Ceria Nyacol was used as a binder to favor the anchoring of catalytic particles thus enhancing the adhesion of the coating. The resulting structured catalysts were tested for the combustion of diesel soot with the aim of being used in the regeneration of particulate filters (DPFs). The performance of these structured catalysts was similar to or even better than that exhibited by the catalysts prepared using commercial nanoparticles. Among the catalysts tested, the structured systems using ceramic substrates were more efficient, showing lower values of the maximum combustion rate temperatures (TM = 410 °C).